Use of gene expression profile to identify potentially relevant transcripts to myofibrillar fragmentation index trait - Muniz, Maria Malane Magalhães [UNESP] (2020)
The myofibrillar fragmentation index (MFI) is an indicative trait for meat tenderness. Longissimus thoracis muscle samples from the 20 most extreme bulls (out of 80 bulls set) for MFI (high (n = 10) and low (n = 10) groups) trait were used to perform transcriptomic analysis, using RNA Sequencing (RNA-Seq). An average of 24.616 genes was expressed in the Nellore muscle transcriptome analysis. A total of 96 genes were differentially expressed (p value ≤ 0.001) between the two groups of divergent bulls for MFI. The HEBP2 and BDH1 genes were overexpressed in animals with high MFI. The MYBPH and MYL6, myosin encoders, were identified. The differentially expressed genes were related to increase mitochondria efficiency, especially in cells under oxidative stress conditions, and these also were related to zinc and calcium binding, membrane transport, and muscle constituent proteins, such as actin and myosin. Most of those genes were involved in metabolic pathways of oxidation-reduction, transport of lactate in the plasma membrane, and muscle contraction. This is the first study applying MFI phenotypes in transcriptomic studies to identify and understand differentially expressed genes for beef tenderness. These results suggest that differences detected in gene expression between high and low MFI animals are related to reactive mechanisms and structural components of oxidative fibers under the condition of cellular stress. Some genes may be selected as positional candidate genes to beef tenderness, MYL6, MYBPH, TRIM63, TRIM55, TRIOBP, and CHRNG genes. The use of MFI phenotypes could enhance results of meat tenderness studies.